Gosnell : [videorecording (DVD)] the trial of America's biggest serial killer - Searcy, Nick; Cain, Dean; Turner, Janine, 1963-; Morris, Sarah Jane; Beach, Michael; McElhinney, Ann (GVN Releasing, 2019)
The film is the shocking true story of the investigation and trial of Dr. Kermit Gosnell - his 30 year killing spree and the political and media establishment that tried to cover it up. Originally investigated for illegal prescription drug sales, a raid by DEA, FBI & local law enforcement revealed crimes they could not have expected within the clinic.